In vitro production of porcine zygotes using intracytoplasmic injection of vitrified sperm. (21st April 2017) - Arraztoa, CC; Baca Castex, C; Alvarez, GM; Cetica, PD; Neild, DM
Contents: The objectives of this study were to evaluate if vitrified porcine spermatozoa are able to maintain their capacity to produce zygotes in vitro using intracytoplasmic sperm injection (ICSI) and to evaluate the zygote development in two in vitro atmospheric conditions: 5% CO2 and tri‐gas. A group of porcine oocytes maturated in vitro were injected with vitrified‐warmed sperm (treatment group) and another group, with sperm diluted and conserved at 17°C (control group). To evidence parthenogenetic activation, some oocytes were submitted to a Sham test. The injected oocytes were cultured in G1 medium at 38°C, 100% humidity and 5% CO2 or tri‐gas. No significant differences ( p > .05) were observed in embryo development between the oocytes injected with vitrified‐warmed sperm (31.8%; 36/113), and those injected with semen diluted and conserved at 17°C (35.5%; 32/90), when cultured in 5% CO2 or under tri‐gas atmosphere (42.9%; 39/91 vs. 34.2%; 26/76, respectively). No significant differences ( p > .05) were observed in the percentage of pronuclei (PN) obtained between 5% CO2 and tri‐gas, within each treatment either. Of the 52 oocytes submitted to the Sham test, only two presented a female PN (activation) indicating that the PN observed in the treatment group were a product of fertilization and not parthenogenetic activation. To conclude, porcine sperm vitrified using spheres, at a concentration of 5 × 10 6 spermatozoa/ml in TALP medium with 1% bovine serum albumin (BSA), conserve condensed and intact chromatin capable of producing early embryo development up to the pronuclear stage.